CAMPUR KODE BAHASA MELAYU DIALEK JAMBI DALAM KOLOM KOMENTAR PADA LAMAN “KABAR KAMPUNG KITO” - Arrabi'ah, Maullinia Resti; Markhamah, Markhamah; Nasucha, Yakub (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
This research aims to describe the types of code-mixing, identify the factors that influence its use, and explain its relation to moral and educational values in the comment section of the Kabar Kampong Kito Instagram account. This study employs a qualitative descriptive method with data collection through documentation techniques and data analysis using distributional and referential methods. The results show that the most dominant type of code-mixing is inner code mixing, which involves mixing Indonesian vocabulary with Jambi dialect Malay within a single utterance. In addition, outer code mixing was also found, involving the insertion of foreign terms such as shock therapy, viral, and goldlane, as well as hybrid code mixing, which combines all three languages in one comment. Identified code-mixing patterns include Jambi-Indonesia-Jambi, Jambi-Indonesia–Jambi–Indonesia-Jambi,Indonesia-Inggris, and Indonesia–Inggris-Jambi.The factors that contribute to code-mixing include local language habits, cultural and social identity, emotional expression, the influence of social media and digital trends, as well as contextual needs in delivering social criticism or satire. Code-mixing serves not only as a means of communication but also as a medium for conveying moral and educational values, such as responsibility, discipline, legal awareness, and character education indirectly. It is also used as a form of cultural participation and preservation of regional identity in the digital space. Thus, the findings indicate that code-mixing is a dynamic and contextual language practice that functions as an educational medium and a reflection of the social and cultural identity of the Jambi community.